2005
DOI: 10.1292/jvms.67.1071
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Study on the Microarchitecture of the Vascular System in the Pigeon Lung

Abstract: ABSTRACT. The resin casts of the respiratory and vascular systems in pigeon lung were examined using a scanning electron microscope. The primary bronchi branched to form many secondary bronchi that anastomosed with each other via the parabronchi. Numerous infundibula protruded from the parabronchi via the atria and ramified into the air capillaries. The pulmonary artery entered into the lung and branched into three vessels that coursed the interparabronchial parts. The intraparabronchial arterioles penetrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Avian lung structure has been reviewed extensively (184, 185, 186, 374, 375, 465, 475, 476, 481, 482, 485, 526, 566). On its dorsolateral aspect, the lung is deeply marked by the vertebrae and ribs (Fig.…”
Section: Section 4 Avian Respiratory System: Transition From Land Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Avian lung structure has been reviewed extensively (184, 185, 186, 374, 375, 465, 475, 476, 481, 482, 485, 526, 566). On its dorsolateral aspect, the lung is deeply marked by the vertebrae and ribs (Fig.…”
Section: Section 4 Avian Respiratory System: Transition From Land Tomentioning
confidence: 99%
“…30A-C). In the chicken, Pigeon and Black-Headed Gull, the infundibulae range from 25 to 40 μm in diameter (471, 501, 566, 815). Air capillaries comprise approximately 52% of total gas-exchange tissue volume (486) and anastomose profusely (Figs.…”
Section: Section 4 Avian Respiratory System: Transition From Land Tomentioning
confidence: 99%
“…Study of histological sections, as performed by Abdalla and King (1975), does not allow direct rendition to the three-dimensional (3D) arrangement: the 3D schemes that are developed pursuant to such studies depend largely on the intuition and judgment of the investigator and may be subject to personal bias. Regarding the casting method that was used by West et al (1977), Maina (1982Maina ( , 1988, and Nasu (2005), the accuracy depends on the suitability and the nature of the material used for injection in relation to the size of the structures that are cast. Artifacts may arise from underfilling, overfilling, or in extreme cases extravasation of the material, after failure of the wall of the conduit (Murakami, 1971;Clark et al, 1979;Ohtani, 1980;Lametschwandtner et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…West et al (1977, p. 557) remarked that the parenehyma showed "a dense, apparently random, three-dimensional 'sponge' of blood eapillaries and air eapillaries"; Duneker (1989) observed that the ACs and BCs form "a sinusoidal three-dimensional network"; Bellairs and Osmond (1998) stated that the parenehyma "resembles a sponge in strueture"; and Makanya et al (2007Makanya et al ( , p. 1142 reported that the parenehyma eomprises "a dexteriously erafted blood capillary network that interfaces with the equally eomplex air eapillary labyrinth." Examination of two-dimensional histologieal seetions by light mieroseopy (LM) and easting have mainly been used in attempts to explieate the morphologies and spatial organization of the ACs and the BCs (e.g., Abdalla and King 1975;West et al 1977;Maina , 1988Nasu 2005). These methods have eertain limitations.…”
Section: Form and Arrangement Of The Acs And Bcs Of The Avian Lungmentioning
confidence: 99%